Putting the local back into planning‐experiences and perceptions of state and district health functionaries of seven aspirational districts in India on an innovative planning capacity building approach. (4th August 2021) - Sarin, Enisha; Bisht, Nitin; Mohanty, Jaya Swarup; Chandra Joshi, Naresh; Kumar, Arvind; Dey, Surajit; Kumar, Harish
Abstract: District functionaries have ostensibly a major responsibility to develop evidence based plans. However, this responsibility is not commensurate with skills and expertise among functionaries in many Indian states. Vriddhi project‐technical partner of the government, developed a planning tool for maternal and neonatal health programmes, called RMNCH + A Action Agenda using Strategic Approach (RAASTA), which was introduced in a workshop format in two states and attended by program officers. Qualitative feedback was obtained from selected participants to understand their experience of the workshop and of the planning tool. It emerged that previous planning process had little application of local evidence based solutions. Participants appreciated the alternative approach as RAASTA equipped them to use local evidence. Several action plans derived at the workshop were included in the state plan. At the same time, apprehension was expressed by participants about translating their learnings to practical application as planning was not a central priority in their scheme of duties and tasks. Enhanced support from states in refreshing district planners' skills would be an important step. One state government has scaled up the RAASTA tool while an electronic version is being developed for future use as it demonstrates great potential to equip and aid district officials in developing evidence based plans.